Prognostic Factors of Severe Community-Acquired Pneumonia in Uttaradit Hospital - Pipatvech, Kanok (Journal of Health Science of Thailand, 2017)
Severe community-acquired pneumonia (SCAP) was the most common causes of in-patient admissions in hospitals. It had high morbidity and mortality. In some difficult cases, many factors were needed for establishment of definite diagnosis and outcome to prediction. The objective of this study was to assess outcomes of treatment and prognostic factors associated with high mortality among SCAP patients. All adult SCAP cases diagnosed by IDSA/ATS criteria, who admitted in Uttaradit Hospital between December 2007and November 2008 were included in this study. The diagnoses of SCAP were consisted of at least 1 of 2 major severity criteria (septic shock and invasive mechanical ventilation)or at least 3 of 9 minor severity criteria. Altogether 257 patients were included in this study. Their mean age was 68.8 years old. Duration of symptoms before admission was 3.7 days. Most of them (76.7%) had co-morbidity; and hypertension was the most common. The most common of symptoms and signs were dyspnea (79.3%) and crepitation (69.3%). About 45% of patients died. The average length of hospital stay was 9.9 days. The most common complication was respiratory failure which needed mechanical ventilator (80.9%). Chlamydophila pneumoniae was the most common causative organisms identified. Septic shock, evident of hypoxemia and CURB 65 more than 3 could be the prognostic factors of increasing mortality in the SCAP patients.